The aesthetics of the iconography of Saudi graffiti art between theory and practice - Nawal Obaidullah Shalian Al alawi (الاكاديمي)
In recent years, Saudi graffiti art has undergone a significant transformation, emerging as a contemporary phenomenon that reflects the cultural and artistic changes in Saudi Arabia. Based on this, the study aims to explore the aesthetics of the iconography of Saudi graffiti art by providing a theoretical framework on the concept of iconography and the features of contemporary Saudi graffiti art.